Recursos educacionais abertos: usos e adaptações no Brasil - Laurentino, Josiane Camacho (2019)
This dissertation discusses the subject of open educational resources and open education. It is a qualitative and exploratory research. It integrates the research projects of the GPTED (Research Group on Educational Technologies) at TIDD — Graduate Program in Technologies of Intelligence and Digital Design of the Pontifical Catholic University of São Paulo (PUC-SP). Its objective is to analyze the scenario of the production and use of open educational resources in Brazil. The methodology included a systematic review of literature, analysis of theoretical texts, analysis of the legislation and a research conducted with users of open educational resources. Concepts such as cyberculture and collective intelligence (Pierre Lévy) are part of the theoretical framework. A questionnaire with open and closed questions was e-mailed to discussion groups participants and made available on platforms and social networks involved in the production and use of open educational resources. The data analysis followed the guidelines of the content analysis of Bardin. The research identified difficulties in locating, identifying and adapting open educational resources. It also identified difficulties in interpreting Creative Commons licenses and understanding the differences between what is open, what is in the public domain and what is free. The study concludes that it is necessary to encourage the creation and maintenance of open educational resources repositories, as well as to develop mechanisms for the evaluation of their quality. Teachers and students, users and producers of open educational resources need guidance and continuing education. These steps are essential for the development of a culture of open education in Brazil